Sharia Compliance dan Islamic Corporate Governance Terhadap Dana Pihak Ketiga Pada Bank Umum Syariah - Annisa Dzahabiyah; Umiyati Umiyati (Department of Accounting-Faculty of Economic and Business (FEB), 2020)
This study aims to analyze the effect of Sharia Compliance and Islamic Corporate Governance on Third Party Funds in Sharia Commercial Banks in Indonesia. The population in this study are Sharia Commercial Banks in Indonesia. Samples were selected using the purposive sampling method. The independent variables in this study are Islamic Income Ratio (IsIR), Proft Sharing Ratio (PSR), Zakat Performing Ratio (ZPR), and Islamic Corporate Governance (ICG). While the dependent variable is Third Party Funds (DPK).The analytical method used is panel data regression with e-views analysis tool 10. The results of this study indicate that the variable Profit Sharing Ratio (PSR) and Islamic Corporate Governance (ICG) significantly influence the Third Party Funds at Islamic Commercial Banks. While the Islamic Income Ratio (IsIR) and Zakat Performing Ratio (ZPR) variables do not significantly influence the Third Party Funds at Islamic Commercial Banks.